Programa de Mobilibidade Acadêmica Internacional da Universidade de Caxias do Sul: desafios linguísticos-culturais dos intercambistas - Rosa, Lisiara Vargas da (My University, 2018)
The purpose of this study is to propose activities that contribute to the Academic Mobility Program of the University of Caxias do Sul - UCS, in order to collaborate with the development of the communicative competence of exchange students received in the Institution. To this end, the concepts of culture, globalization and internationalization based on what is proposed by Pozenatto (2003), Ianni (1994; 2002) and Hall (2001). This research is based on the theoretical assumptions of sociolinguistics, in the studies of Labov (2008), Calvet (2002), Coseriu (1992) and Hymes (1995), shows the intrinsic relationship between language and society. On this basis, proposals for activities aimed at the development of students' communicative competence of exchange students. These activities seek to contemplate the teaching of the language in use, starting, for example, cultural situations typical of the place of passage. In addition, for the preparation of activities, which is proposed by the European Common Frame of Reference for Languages (QCER), specifically for Level B1 proficiency, considered intermediate level. It is concluded with this research that both, cultural studies and sociolinguistics can collaborate so that activities capable of not only to qualify the communicative competence of exchange students, but also to promote to them a meaningful cultural experience.
Este estudo tem como objetivo propor atividades que contribuam com o Programa de Mobilidade Acadêmica da Universidade de Caxias do Sul – UCS, no sentido de colaborar com o desenvolvimento da competência comunicativa de alunos intercambistas recebidos na Instituição. Para tanto, são abordados os conceitos de cultura, globalização e internacionalização a partir do que é proposto por Pozenatto (2003), Ianni (1994, 2002) e Hall (2001). Esta investigação está pautada nos pressupostos teóricos da sociolinguística, em especial, nos estudos de Labov (2008), Calvet (2002), Coseriu (1992) e Hymes (1995), pondo à mostra a intrínseca relação entre língua e sociedade. Com base nisso, são apresentadas propostas de atividades voltadas ao desenvolvimento da competência comunicativa de alunos intercambistas. Essas atividades procuram contemplar o ensino da língua em uso, partindo, por exemplo, de situações culturais típicas do local de passagem. Além disso, é considerado, para elaboração das atividades, o que é proposto pelo Quadro Comum Europeu de Referência para Línguas (QCER), especificamente no que se refere ao Nível B1 de proficiência, considerado nível intermediário. Conclui-se com essa pesquisa que tanto os estudos culturais quanto a sociolinguística podem colaborar para que sejam produzidas atividades capazes não só de qualificar a competência comunicativa de alunos intercambistas, mas também propiciar a eles uma experiência cultural significativa.
Keywords: Programas de intercâmbio de estudantes; Linguagem e línguas; Cultura; Student exchange programs; Language and languages; Culture